Evaluación de la concentración de NO2, SO2 en el aire y su relación con el perfil epidemiológico en la población de Segunda Jerusalén - Chicana Vargas, Mariano (2006)
The evaluation of NO2 and SO2 concentration in the air and its relation with the change in the epidemiologist profile of the population in Segunda Jerusalén is a research work, where we show some information about the condition of the air people are breathing in Segunda Jerusalén district, in adition, about the morbidity by Acute Respiratory Infections (ARI). The research was done inside the houses (intra domiciliary), and the analysis of ARI is about information of the last eleven years and the cases are classified according to age group and gender. The air which settlers of Segunda Jerusalén breathe presents polluting gases with Nitrogen Dioxide and Sulfur Dioxide, but the concentrations don’t exceed the national and international enviromental quality standars, although the first one is in greater concentration. In the evaluation of the Acute Respiratory Infections in a period of eleven years (1995 –2005), it’s concluded that they are the main health problems of children under 9 yers old, constituting itself in one of the first causes of morbidity which has been increased considerably since 1998. The results of this evaluations show us the presence of polluting gases and the increase of morbidity by ARI, that’s why we consider the proposal of control of the atmospheric pollution as a plataform which helps to define the actions to conserve the air quality in Segunda Jerusalén. For example: monitoring of pollution gases concentrations, like NO2, SO2, CO2 and O3, PTS y PM- 10, stablished in the peruvian law D.S. N° 074-01-PCM, without excluding the monitoring of other pollution agents, like noise.Another proposed action is to stablish and to keep updated the inventory of polluting emissions from stationary and mobile sources and others which have more importance, with the purpose of keeping the concentrations levels or decreasing them and making its completion easier, and finally, to use the appropiate instruments and techniques to formulate predictions about the future variations of the air quality and this way, to be abble to consider the impact of the adopted control measures and their relation :cost – benefit.